About Law Enforcement - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2021)
The article examines a number of features of law enforcement in the law enforcement sphere. In particular, the author touched upon the subject composition of law enforcement activities, as well as its participants (victims, witnesses, etc.), on whose legal activity the effectiveness of law enforcement activities largely depends. Attention is drawn to the professional and psychological culture of law enforcement entities, to the regulatory framework of law enforcement, and its peculiarities. stages, structure of law enforcement acts.